2010
DOI: 10.1063/1.3524500
|View full text |Cite
|
Sign up to set email alerts
|

Observation of large electric polarization in orthorhombic TmMnO3 thin films

Abstract: High-quality orthorhombic (OT) TmMnO3 (TMO) thin films with a-axis perpendicular to the film surface are grown epitaxially on Nb-doped SrTiO3(110) substrates using pulsed laser deposition. The structural, magnetic, and electric properties of OT-TMO films are measured. We found that a strong coupling between the magnetic structure and the electric polarization. Our experimental results also show that ferroelectricity in OT-TMO thin films below 32 K. Furthermore, the large electric polarization up to 0.45 μC/cm2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
2
17
1
Order By: Relevance
“…Since the P − E curve does not saturate up to E = 7 kV/cm, a larger saturated P is to be expected, which could be measured with higher poling fields (or using thin films). 12,13 In addition, a tiny anomaly in the pyroelectric current emerges at T N2 under E = 7 kV/cm, as shown in Fig. 4(a), which gives rise to a small increase of P .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Since the P − E curve does not saturate up to E = 7 kV/cm, a larger saturated P is to be expected, which could be measured with higher poling fields (or using thin films). 12,13 In addition, a tiny anomaly in the pyroelectric current emerges at T N2 under E = 7 kV/cm, as shown in Fig. 4(a), which gives rise to a small increase of P .…”
Section: Resultsmentioning
confidence: 93%
“…For instance, the predicted FE P in the E-type AFM manganites is of the order of 10000 µC/m 2 , 9,10 which has been recently confirmed in experiments. [11][12][13] However, the FE T C 's of the E-type AFM manganites remain low (typically ∼ 30 K) 11 due to the magnetic frustration, namely the competition between nearest-neighbor (NN) and next-nearestneighbor (NNN) exchange interactions.…”
Section: Introductionmentioning
confidence: 99%
“…One is the spatial inverse symmetry breaking induced by the spin-orbit coupling (SOC) via the inverse Dzyaloshinskii-Moriya (DM) interaction or equivalently the super spin current scenario [12,13], mainly identified in 3d magnetic transition metal oxides of noncollinear spin order [14,15]. The other is the spin-lattice coupling associated with collinear, typically the ↑↑↓↓ spin order, or E-type antiferromagnetic (AFM) order, which breaks the inverse symmetry too [16][17][18]. In particular, those multiferroics of noncollinear spin order have been intensively addressed in past several years partially because the ferroelectricity is associated with the SOC via the DM interaction, allowing very strong magnetoelectric (ME) coupling [6].…”
Section: Introductionmentioning
confidence: 99%
“…As the orthorhombic phase of RMnO 3 with R¼Y, Ho-Lu is not a thermodynamically stable phase at the ambient conditions, obtain of o-RMnO 3 (R¼Y, Ho-Lu) is therefore a prerequisite for the follow-up studies. Epitaxial stabilization of this orthorhombic phase in thin films were achieved by metal-organic chemical vapor deposition (MOCVD) [3] and pulsed laser deposition (PLD) [4][5][6]. Meanwhile, recent studies have reported the strain-induced effects on ferroelectricity [7], magnetic ordering [8], magnetocapacitance [9], and magnetoelectric coupling [10] in o-RMnO 3 thin films.…”
Section: Introductionmentioning
confidence: 98%
“…Meanwhile, recent studies have reported the strain-induced effects on ferroelectricity [7], magnetic ordering [8], magnetocapacitance [9], and magnetoelectric coupling [10] in o-RMnO 3 thin films. Large electric polarization and magnetoelectric coupling have just been found in o-TmMnO 3 (o-TMO) thin films [6]. In order to have a better understanding of the physical properties of these materials and the mechanisms involved, it is of vital importance to analyze the microstructure of o-RMnO 3 (R¼ Y, Ho-Lu) thin films.…”
Section: Introductionmentioning
confidence: 99%